Pengaruh kompensasi dan kompetensi tenaga pelatih terhadap kinerja tenaga pelatih dan motivasi sebagai variabel intervening di UPTD BLK Barito Kuala - Rahayu, Sri; Surachmad, Surachmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to explain the effect of compensation and competence on the motivation of the trainers and the effect of compensation, competence and motivation on the performance of the trainers. This research was conducted at UPTD BLK Barito Kuala and the population in this study were trainers. The sample used is total sampling, namely all 32 trainers. Methods of data collection using a questionnaire via google form. The data analysis technique used is Path Analysis with the Smart PLS 3.0 application. The results of this study indicate that compensation has a positive and significant effect on the motivation of the trainers, competence has a positive and significant effect on the motivation of the trainers, compensation has a positive and significant effect on the performance of the trainers. While competence has no effect on the performance of the trainers, motivation has no effect on the performance of the trainers and motivation is not able to mediate the effect of compensation and competence on the performance of the trainers.